Clinical Guide to Heart Transplantation - Kobashigawa, Jon (Springer International Publishing : Imprint: Springer, 2017)
This handbook is an easy reference for those involved in the management of heart transplant. While this compilation of best practices cannot address the complexity of the individual patients we care for on a daily basis, it will serve to help us ask the right questions, access the best evidence and ultimately make the best decisions for the patients involved. Clinical Guide to Heart Transplantation provides a current review of the field of heart transplantation and how it has evolved into an established therapy for the treatment of end-stage heart failure. With the advent of improved surgical techniques, the development of immunosuppressive drugs and the utilization of more sophisticated monitoring strategies and treatments for graft rejection, heart transplantation now offer patients an avenue to both improved survival and quality of life. With over 4000 heart transplants performed per year globally and with 1-year survival approaching 90%, this practical title assists those involved in the this most complex of procedures to establish best practice. It is therefore essential reading for all practitioners in this field, charged with making critical decisions in the management of patients, donor organs, and the transplant process itself in order to achieve the greatest benefit in the utilization of this often scarce resource.
Keywords: Medicine.; Cardiology.; Cardiac surgery.; elektronické knihy; electronic books